Chattanooga, 1865-1900 : A City Set Down in Dixie - Ezzell, Tim (Book collections on Project MUSE., 2013)
After the Civil War, the city of Chattanooga, Tennessee, forged a different path than most southern urban centers. Long a portal to the Deep South, Chattanooga was largely rebuilt by northern men, using northern capital, and imbued with northern industrial values. As such, the city served as a cultural and economic nexus between North and South, and its northern elite stood out distinctively from the rest of the region's booster class. In Chattanooga, 1865-1900, Tim Ezzell explores Chattanooga's political and economic development from the close of the Civil War through the end of the nineteenth century, revealing how this unique business class adapted, prospered, and governed in the postwar South. After reviewing Chattanooga's wartime experience, Ezzell chronicles political and economic developments in the city over the next two generations. White Republicans, who dominated municipal government thanks to the support of Chattanooga's large African American population, clashed repeatedly with Democrats, who worked to "redeem" the city from Republican rule and restore "responsible," "efficient" government. Ezzell shows that, despite the efforts by white Democrats to undermine black influence, black Chattanoogans continued to wield considerable political leverage into the 1890s. On the economic front, an extensive influx of northern entrepreneurs and northern capital into postwar Chattanooga led to dynamic if unstable growth. Ezzell details the city';s efforts to compete with Birmingham as the center of southern iron and steel production. At times, this vision was within reach, but these hopes faded by the 1890s, and Chattanooga grew into something altogether different: not northern, not southern, but something peculiar "set down in Dixie." Although Chattanooga never reached its Yankee boosters' ideal of "a northern industrial city at home in the southern hills," Ezzell demonstrates that it forged a legacy of resilience and resourcefulness that continues to serve the community to the present day